Training on the Formulation of Marketing Strategies for Organic Green Onions (Allium fistulosum L.) - Suswadi; Ismail Aji Eko Cahyono (Universitas Tunas Pembangunan Surakarta, 2023)
The village of Gedangan in the Cepogo sub-district of Boyolali Regency is renowned for being a producer of organic vegetables and has obtained Organic Farming SNI certification. Marketing strategy is a fundamental aspect planned to achieve business goals by continuously enhancing competitive capabilities. As a result, crafting a marketing strategy is crucial for the farmer group. In this community engagement, the farmer group is trained to develop marketing strategies for organic vegetables using the SWOT method. Based on the training outcomes and the practical analysis of the marketing strategy for organic scallions, the leaders and farmer representatives now understand the importance of devising a marketing strategy for organic vegetable products in order to foster sustainable product marketing growth. Training participants are also capable of conducting SWOT analyses to formulate marketing strategies for organic agricultural produce, even though further training is necessary to enhance the skills of the farmer group leaders.